Language teaching in the kindergarten effective or an unnecessary burden? - Balta Georgina (2002)
This thesis examines how effective is language teaching in the kindergarten at the age of 5 and 6. My aim is to prove that early childhood is the best age to make children like foreign language. We should use up their excellent listening skills and the ability to pronounce English words without any difficulties. I will describe how a regular English lesson goes in the kindergarten where I teach, and I will also write down my experiences of the effectiveness of my work. I will demonstrate that language learning can be effective despite the young age of children.